The association between academic performance and sleep quality and quantity among health sciences college students - Aldoraissi, Hussain; Istad, Mustafa; Alhakeem, Mohammed; Nabzah, Ahmad; Alsubogh, Khaled; Hatem A. Alqahtani; Alharkan, Khalid; Alqurashi, Yousef D. (Acta Biomedica Atenei Parmensis, 2024)
Background and aim of the work: The relationship between sleep and academic performance in Undergraduate health sciences college students have not been adequately addressed in the literature. This study aimed to investigate the association between sleep duration and quality with students’ academic performance measured by cumulative grade point average (GPA). Research design and Methods: The sample consists of students from health Sciences colleges at Imam Abdulrahman Bin Faisal University (IAU), Dammam, Saudi Arabia. The data were collected through random sampling using Pittsburgh Sleep Quality Index (PSQI) in both Arabic and English language. The academic performance of the students was measured using their average GPA. The chi-square, t-test, and ANOVA tests were used to examine the relationship between sleep quality and duration and Academic performance. Results: In total, 448 students were recruited, of which 45% were males (n=200) with a mean age of 21±1 years. The average GPA calculated was 4.21±0.4. The students with GPA above 4.21 are considered higher achievers. There was a significant difference between sleeping hours at night and GPA (p-value = 0.034). There was no significant difference between sleep quality and GPA (x2= 0.150, p value = 0.903). Conclusions: Our data suggests that students who sleep 6 to 7 hours are academically better performers with higher GPA than those with less hours of sleep. Therefore, students at higher education institutions should be encouraged to have adequate sleep to get better grades in their courses.